Antimicrobial activity of secondary metabolites isolated from endophytic fungi associated with rubiaceae species / Sadia Sultan ... [et al.] - Sultan, Sadia; Mohd Ali, Khairun Azwani; Mohamed Akram, Noor Dayana; Ashraf, Kamran; Ashraf, Muhammad; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2022)
The effectiveness of antibiotics has declined significantly due to development of drug resistance. Consequently, it results in millions of deaths due to infectious diseases. Many studies have suggested that bioactive compounds produced by endophytes could be an alternative to discover new antimicrobial compounds. Endophytes are microorganisms that reside within the tissues of living plants that cause no apparent harm to the host. Fungal endophytes may biosynthesize the same or similar compounds as their host plant and other diverse bioactive compounds, which provide various pharmacological activities. Therefore, this study aimed to conduct literature search on the antimicrobial properties of the isolated compounds produced by fungal endophytes associated with Rubiaceae. Literature was conducted on secondary metabolites of endophytic fungi via four databases; EBSCOhost, Google Scholar, PubMed, and Scopus. A search filter was performed to include only research articles from 2007 to 2021. The search was restricted to publications in English only. Overall, 29 publications were selected for full-text evaluation and were included in the study. Results showed that sixteen antimicrobial metabolites were isolated from six fungal endophytes of ten different plant species were identified. These compounds were classified as alkaloid, phenol, coumarin, steroid, diterpene, and meroterpene.